Investigating the timing of postrift extension in northern New England: crosscutting structures at the early Cretaceous Cuttingsville Complex, Vermont - Barrientos, Gaby; Fatimah, Areebah; Boemmels, Jennifer (Abstracts with programs - Geological Society of America, 2025)
Keywords: Computer science; Cretaceous; Extension (predicate logic); Geology; Paleontology; Programming language; dept.esc

40Ar/39Ar and LA-ICP-MS U–Pb geochronology for the new england portion of the early cretaceous new england-quebec igneous province: Implications for the postrift evolution of the eastern north american margin - Boemmels, Jennifer Cooper; Crespi, Jean M.; Webb, Laura E.; Fosdick, Julie C. (American Journal of Science, 2021)
The Early Cretaceous New England-Quebec igneous province is a classic example of postrift magmatism along the eastern North American passive margin. Although a suite of 40Ar/39Ar ages has been available for the Monteregian Hills lobe in the Quebec portion of the New England-Quebec igneous province for many years, only a single high accuracy radiometric age has been published for the Burlington lobe and none for the Taconic lobe in the New England portion of the province. As a result, the timing of and driving mechanisms behind the magmatism have remained unresolved, and a hotspot origin for the entire province persists in the literature. We have dated four dikes and one pluton in the Burlington and Taconic lobes using 40Ar/39Ar and U-Pb geochronology to improve understanding of the age of magmatism in the New England portion of the province. In the Burlington lobe, 40Ar/39Ar plateau ages include a 137.55 ± 1.80 Ma biotite age and a 136.9 ± 4.2 Ma amphibole age for a lamprophyre dike from Charlotte, Vermont, and a 133.6 ± 2.2 Ma biotite age for a lamprophyre dike from Colchester, Vermont. In the Taconic lobe, ages include an 40Ar/39Ar plateau amphibole age of 107.09 ± 1.32 Ma for a lamprophyre dike from Castleton, Vermont, a 122 Ma minimum 40Ar/39Ar biotite age for a lamprophyre dike from Poultney, Vermont, and a 103.13 ± 0.53 Ma LA-ICP-MS U-Pb zircon age from the quartz syenite of the Cuttingsville complex. These results show that magmatism spanned at least 35 Ma, from 138 to 103 Ma, which is broadly consistent with the span of magmatism suggested by workers in the 1970s and 1980s based on K-Ar and Rb-Sr ages. This extended span of magmatism for the Burlington and Taconic lobes is in contrast to the brief 1 to 2 Ma episode of magmatism at 124 Ma inferred for the Monteregian Hills lobe. The New England- Quebec igneous province has traditionally been attributed to passage of the Great Meteor hotspot. However, given the close proximity of the Burlington and Taconic lobes, the magmatism in these lobes should span only a few Ma if the product of a hotspot. The age data are also difficult to reconcile with a more complex expression of hotspot magmatism in continental lithosphere related to either plume head magmatism or long-distance migration of plume material. Instead, the extended duration of Early Cretaceous New England-Quebec igneous province magmatism in New England may represent an expression of edge-driven convection, a process known to occur along passive margins and inferred to be operating beneath the eastern North American margin today. © 2021 American Journal of Science. All rights reserved.
Keywords: Canada; Cretaceous; New England; Quebec [Canada]; United States; argon-argon dating; dept.esc; geochronology; igneous province; inductively coupled plasma method; magmatism; mass spectrometry; passive margin; peer-reviewed; rifting